Moral Education Management for Santri at Dayah Nurul Kamal Al-Aziziyah Aceh Utara - Ibnu Sakdan (Wasatha: Jurnal Studi Islam dan Humaniora, 2024)
Morals is an education that is not easy to apply to a person’s character, especially students. This is because there are many influences from various lines that can form one’s attitude, mindset, and knowledge so that it has an impact on the formation of negative morals in the younger generation. Therefore, the importance of education management in shaping the morals of students so that they can mold the younger generation to have good morals. The objectives of this study include: 1) knowing the management of students’ moral education at Dayah Nurul Kamal Al-Aziziyah, North Aceh Regency, 2) knowing the application of students’ moral management at Dayah Nurul Kamal Al-Aziziyah, North Aceh Regency, 3) knowing the output of santri graduates Dayah Nurul Kamal Al-Aziziyah, North Aceh District. This study uses descriptive qualitative methods by describing phenomena that occur in the field and analyzed using existing theories. The results of the study show that: 1) Dayah Nurul Kamal Al-Aziziyah has an important role in producing students with good morals through activities such as the taklim al-Hikam assembly, learning to read and teaching the yellow book ta’limul muta’allim, Madin, and TPQ . 2) In implementing existing programs, Dayah Nurul Kamal Al-Aziziyah with all ustadz and ustadzah have made maximum efforts even though there are several supporting and inhibiting factors. 3) The output of Dayah Nurul Kamal Al-Aziziyah graduates is very good by contributing to society and the development of Dayah. In this case the Dayah leadership provided an alumni forum called Rabithah Alumni Dayah Nurul Kamal Al-Aziziyah (RABUKA).